OPTIMISATION OF THE MIXTURE OF ACTIVATED CHARCOAL AND RED GINGER EXTRACT WITH THE ADDITION OF SANSEVIERIA TO THE FOOD CABINET FILTER - Astuti, Siswi; F. Endah Kusuma Rastini; Ester Priskasari; Djoko Hari Praswanto (Journal of Sustainable Technology and Applied Science (JSTAS), 2023)
Spoiled or unhealthy food is the causative agent of a disease called ptomaine poisoning. This disease can come from consuming water, milk, other drinks, or food in raw or cooked form provided in a place that contains agents that can produce disease in sufficient quantities—an amount needed to cause various diseases. Various agents that can cause disease in food are plants, bacteria, chemicals, animals, agents that use food as a means of transferring themselves, radionuclides, and microbes. Food damage caused by microbes is usually due to the condition of the food, which has a high water content, improper storage of food, or types of food that are not durable. Microbes that cause harm can come from slime molds, yeasts, bacteria and viruses in a variety of ways. Can come from polluted air, cross-contamination from food storage areas. The purpose of this research is to make an air filter in a food storage cupboard that has the optimum ability to inhibit the growth of pathogenic microbes so that the stored food is not easily damaged. The method of implementation in this study was to make a filter mixture composition consisting of activated charcoal from bamboo ori, sanseviera, and red ginger extract, where the material has anti-bacterial and antiviral benefits. The filter composition to be tested is a mixture of activated charcoal, sanseviera, and ginger extract. red in the ratio: 3:1:4; 4:1:4; 4:1:3; 2:2:4; 4:2:4; 4:2:2, samples containing protein. The best results that can inhibit the growth of Bacillus substillis are obtained in filters with a composition of 4:2:4.